Orientations in learning English as a foreign language: How do Indonesian students view them? - Kaspul Anwar; M. Faruq Ubaidillah; Veronico N. Tarrayo; Febti Ismiatun; Khusnul Khotimah; Irawansyah Irawansyah; Urip Sulistiyo (Universitas Islam Sultan Agung, 2020)
Anchored by the scant studies on Indonesian junior high school students’ orientation in learning English as a foreign language, this present study showcased how their learning orientation, delved into integrative and instrumental orientation models, was enacted. 144 students were recruited to answer an integrative and instrumental orientation 20-item questionnaire adapted from Attitude Motivation Test Battery (AMTB). Findings suggested that in terms of integrative orientation, the participants viewed learning English as a gateway to knowing and understanding native speakers’ cultural norms. This tenet was echoed by the global spread of English. In terms of instrumental orientation, the participants believed that learning English assisted them in career advancement. The results of this study concluded that the students, despite positively favored in learning English, leaned their English learning orientation on the native speakerism issue and the global spread of English.